Rendre audible la voix d’une rescapée tutsie : le rôle du paratexte dans Le Livre d’Élise - MacLeod, George (Études littéraires africaines, 2015)
This article uses trauma theory to show the unique paratextual framing of Tutsi genocide survivor Élise Rida Musomandera’s memoir, Le Livre d’Élise (Les Belles Lettres, 2014). While dozens of survivor accounts from the Tutsi diaspora have been published in the last two decades, Musomandera’s is the first eye-witness memoir written by a Tutsi survivor still living in Rwanda. The vast majority of these testimonial memoirs contain introductions and postfaces which present the text for a Western reader. These paratexts have tended to privilege one of two discourses, comparing the Tutsi survivor’s story either to a moral lesson or to Holocaust testimonies. In contrast, the introduction to Le Livre d’Élise emphasizes the encounter between Musomandera’s authorial voice and the reader. The introduction’s European co-authors suggest that in reading Musomandera’s text, the reader joins a community of attentive interlocutors who are participating in the ongoing process of helping her find agency and social recognition following the devastating impact of genocide.